2014
DOI: 10.1371/journal.pgen.1004359
|View full text |Cite|
|
Sign up to set email alerts
|

A Dominant-Negative Mutation of Mouse Lmx1b Causes Glaucoma and Is Semi-lethal via LBD1-Mediated Dimerisation

Abstract: Mutations in the LIM-homeodomain transcription factor LMX1B cause nail-patella syndrome, an autosomal dominant pleiotrophic human disorder in which nail, patella and elbow dysplasia is associated with other skeletal abnormalities and variably nephropathy and glaucoma. It is thought to be a haploinsufficient disorder. Studies in the mouse have shown that during development Lmx1b controls limb dorsal-ventral patterning and is also required for kidney and eye development, midbrain-hindbrain boundary establishment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…Furthermore, recent studies in mice have demonstrated that missense variants of the HD can show dominant-negative activity in vivo. 15 In the present study, we describe the phenotype and molecular data of 55 index patients and their 39 relatives affected with NPS. Variants or large rearrangements of LMX1B were identified in 91% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies in mice have demonstrated that missense variants of the HD can show dominant-negative activity in vivo. 15 In the present study, we describe the phenotype and molecular data of 55 index patients and their 39 relatives affected with NPS. Variants or large rearrangements of LMX1B were identified in 91% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…71 A dominant negative mutation of mouse Lmx1b (Lmx1b Icst/+ ) also causes glaucoma and is semi-lethal. 72 The COL19A1 gene encodes the alpha chain of type XIX collagen, a member of the FACIT collagen family (fibril-associated collagens with interrupted helices). Decreased expression of Col19A1 (1.9 fold) was observed in a microarray of an 8-month old DBA/2J mouse retina when compared to 3-month-old retina.…”
Section: Discussionmentioning
confidence: 99%
“…An N-ethyl-N-nitrosourea-induced missense substitution, V265D, in the homeodomain of mouse Lmx1b abolishes DNA binding and causes glaucomatous eye defects in heterozygotes. A profound reduction in the number of retinal ganglion cells and optic nerve cupping was observed in some cases [147].…”
Section: Lmx1bmentioning
confidence: 98%